Adolescentes grávidas: percepções e educação em saúde - Danieli, Guiomar Luciana (2010)
Adolescence is the transitional period between childhood and adulthood, occurring between 10 and 19 years old. The development of sexuality is part of the adolescent s universe and it s essential that occurs in a healthy way, because one of the consequences that may result from this development is the early pregnancy. The teenage pregnancy is a reality in our society, caused by factors such as lack of education actions in health, absence of a specific attention policy to this age group as well as social and cultural components. The results of a pregnancy at that age, desired or not, are related to the girls s physical, emotional, educational and socio-cultural components. However, it identifies in the health services several adolescents who report a desire to become pregnant. Therefore, the objectives of this study were to understand the meaning of pregnancy for adolescents; to know the experience of pregnant teenagers related to health education; understand how the educational practices developed in a group of health education with pregnant teenagers may contribute to the construction of their emancipation. A qualitative approach was used by Convergent-Assistencial Research, as a method and a strategy for the practice of health education. The study was conducted at the Basic Health Unit Vila Ipe, in the city of Caxias do Sul / RS. The study participants were 13 pregnant under 20 years who were performing outpatient prenatal care at BHU. The period of data collection and implementation of educational groups was from June to October, 2009. It were identified feelings as happiness, excitement, responsibility, fear, anxiety, maturity, insecurity, among others. Most dropped out the studies because of pregnancy, and go back to school didn t appear as a priority. The family reactions to the pregnancy were surprise, joy and disgust, depending on factors such as knowledge or ignorance of the family in relation to the sexual activity of teenagers and existence of stable union. The main support after the birth of the baby is from their mothers. Related to previous experiences of health education, most teens had memories of lectures or guidance received at school, whose themes were related to sexuality, sexually transmitted diseases or teenage pregnancy. In addressing the use of contraceptives, the majority demonstrated knowledge of contraceptive methods, however, there was insufficient information, no understanding of their use or even the conscious or unconscious desire to become pregnant. It was also shown the importance of educational groups as a tool for health education, especially in the stimulation or enhancement of autonomy in decision making, particularly with the use of an active methodology. We believe in the relevance of this work by allowing a reflection of the peculiarities of adolescence, as well as the need to develop health education actions based not only on these peculiarities, but also on the experiences and desires of adolescents. We hope it will help in the care of nursing, as a tool for reflection and reorganization practice, seeking evercloser relationship with the universe of adolescence.